Analisis Perbandingan Return dan Risk Investasi Saham Syariah dan Konvensional yang Terdaftar pada Bursa Efek Indonesia - Nurlia Safitri; Heriyati Chrisna (Masyarakat Ekonomi Syariah Bogor, 2025)
Sharia and conventional stock investments each have different return and risk profiles, where sharia stocks tend to have lower volatility because they are limited by sharia principles but still have the potential to provide competitive returns. This research aims to analyze the comparison of returns and risks between sharia and conventional shares listed on the Indonesia Stock Exchange for the 2019-2023 period. The research sample consisted of 30 JII sharia shares and 30 IDX30 conventional shares selected using the purposive sampling method. Data analysis uses calculations of realized return, expected return, standard deviation, and independent sample t-test. The research results show: (1) The average return on sharia shares is 12.3% higher than conventional shares of 10.1%; (2) The risk level of sharia shares as measured by a standard deviation of 2.8% is lower than conventional shares of 3.4%; (3) There is a significant difference between the returns and risks of sharia and conventional stocks at a significance level of 5%. The research concluded that sharia stock investment provided higher returns with lower risk than conventional stocks during the research period.